The Effect of Organizational Trust and Job Satisfaction on Teachers’ Organizational Citizenship Behavior (OCB) in Private Senior High Schools - Hidayat, Rais; Patras, Yuyun Elizabeth (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This research aims to investigate and describe the variables that positively influence teachers' OCB so that if the variable is improved, the OCB will increase. This research method begins with determining the conceptual model of teacher OCB, organizational trust, and job satisfaction, whose model is built based on logical validity, concepts, theories, and previous research. Then the conceptual model was tested using path analysis on SMART PLS. This research was conducted at private senior high schools in West Java, Indonesia; the number of samples was 256, determined through multistage proportional random sampling. The findings of this research are: organizational trust affects teacher OCB; organizational trust affects job satisfaction; job satisfaction affects teacher OCB; organizational trust has a positive and significant indirect effect on teacher OCB. This research implies that improving teachers' OCB can be done through improving organizational trust and job satisfaction, including strengthening environmental influences, demonstrating integrity, competence, and policies of the school, improving welfare payments, promotion, supervision, and improving the work atmosphere.